Factors affecting conception after synchronization with Lutalyse® and timed insemination - King, M.; Kiracofe, G.H.; McKee, R.M. (Kansas State University. Agricultural Experiment Station, 2011)
With heifers given two injections of Lutalyse 11 days apart, and inseminated 80 hours after the second injection, only 20% in heat before 48 hours conceived compared with 65% that were in heat 48 to 80 hours after injection. Those showing heat early may have been inseminated too late. Heifers receiving their second injection on day 7. 8, or 9 of the cycle came into heat earlier than those injected on days 10 through 15.
Keywords: Beef; Lutalyse; Synchronization; Insemination